Commemorating economic crisis at a liminal site: Memory, creativity and dissent at Achill Henge, Ireland. (June 2020) - Edensor, Tim; Smith, Thomas SJ
This paper draws on a case study of Achill Henge, County Mayo, Ireland, to examine the interplay between economic crisis, rebel creativity and shifting geographies of commemoration. Built in 2011 in a remote part of the west of Ireland, Achill Henge is a highly contested monument. Unfinished and under perennial threat of demolition, the Stonehenge-like structure was originally conceived as a 'tomb of the Celtic Tiger', in reference to Ireland's ill-fated economic 'miracle' of the 1990s and 2000s. This paper examines this economic context before adopting two perspectives. Firstly, drawing on critical ideas about commemoration, we identify how the Henge remembers economic and political failure, materialising a unique site of subaltern memory. Situating it within memorial landscapes in Ireland, we explore how it can serve to critically analyse practices of traditional and contemporary commemoration. Secondly, we examine how its unsanctioned liminality produces a valuable, exemplary site at which numerous unregulated, playful, performative and political practices can be carried out, away from mainstream convention and commercial banality.